THE HUMOR STORY IN TEACHING READING COMPREHENSION - Tang, Syamsu; Asrifan, Andi; Chen, Yan; Haedar, Haedar; Agussalim, Mutmainnah (JOURNAL OF ADVANCED ENGLISH STUDIES, 2019)
The objective of the research were to find out whether or not the use of Humor Story can improve the students’ reading comprehension and Students interest at the Eighth of SMP Negeri 4 Pancarijang. This research employed a mixed method that applied monolingual class. The population of this research was the eighth grade students in academic year 2018-2019. There were 65 students spread in 3 classes ( VIII.1, VIII.2, and VIII.3) and each class consist appropriately 20-22 students. The researcher took simple random and chose VIII.2 as the representative and the number of total sample is 21 students. The data of the research were collected by using two kinds of instruments, namely reading comprehension test and questionnaire. Reading test was used to obtain data of the students’ reading comprehension ability and questionnaire was used to know the students interest in Reading Comprehension by using Humor Story. The result of data analysis showed that there was significant difference between the students’ score after they were taught by using Humor Story and before they were taught by Humor Story. It was proved by the mean score of the post-test which was higher than the mean score of pre-test (57.57>40.33). Furthermore, the result of the p-value (0.000) was lower than level of significant (α = 0.05); which means that H1 was accepted. Then, the analysis of interest by using Likert Scale indicated that teacing reading comprehension by using humor story, the students were interested. It was proved by 57% students who were strongly interested, 33% students who were interested and 10% students who were moderate. Based on data analysis, the research concluded that: (1) the use of Humor Story effective in improves students’ reading comprehension; (2) the use of Humor Story makes the students interested to learn reading comprehension